2017
DOI: 10.5530/pc.2017.1.4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of anti-inflammatory and antioxidant effects of Asparagus aphyllus L., Crataegus azarolus L., and Ephedra alata Decne.in monocultures and co-cultures of HepG2 and THP-1-derived macrophages

Abstract: Introduction: Asparagus aphyllus L.,Crataegus azarolus L., and Ephedra alata Decne.have been used in traditional Greco-Arab herbal medicine to treat various metabolic and inflammatory diseases. However, to our knowledge, no scientific evidences regarding their anti-inflammatory effects have been published yet.This study aimedto evaluate the antioxidant and anti-inflammatory properties of Asparagus aphyllus L., Crataegus azarolus L., and Ephedra alata Decne.extracts using in vitro mono and co-culture systems. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…But going through the ethnomedicinal literatures, it appears that most of the scientists (Cano & Volpato, ; Kmail, Lyoussi, Imtara, Zaid, & Saad, ; Patwardhan, Vaidya, & Chorghade, ; Zaid, Said, Hadieh, Saad, & Bashar, ) have described “Halion” under the quite different botanical names. Another point to be noted is that in a few recent publications of Unani” Materia Medica” some scholars have given Lepidium apetalum as the source of “Halion”, whereas the other writers mentioned Asparagus officinalis as the source of “Halion”.…”
Section: Resultsmentioning
confidence: 99%
“…But going through the ethnomedicinal literatures, it appears that most of the scientists (Cano & Volpato, ; Kmail, Lyoussi, Imtara, Zaid, & Saad, ; Patwardhan, Vaidya, & Chorghade, ; Zaid, Said, Hadieh, Saad, & Bashar, ) have described “Halion” under the quite different botanical names. Another point to be noted is that in a few recent publications of Unani” Materia Medica” some scholars have given Lepidium apetalum as the source of “Halion”, whereas the other writers mentioned Asparagus officinalis as the source of “Halion”.…”
Section: Resultsmentioning
confidence: 99%
“…Significant cytotoxic effects were recorded for concentrations higher than 500 μg/mL. The cytostatic activity was stronger in the co-cultures (an IC 50 of 380 μg/mL) [27]. Mendelovich et al have shown that ethanolic extracts from the leaves, as well as the fruit juice, of Ephedra foeminea have significant antiproliferative and pro-apoptotic potential against MDA-MB-231 (human breast cancer), HCT116 (human colon) and HaCaT (human keratinocytes) cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the cellular antioxidant activity of C. pinnatifida (Chinese hawthorn) was reported as being derived from the interaction between phenolic compounds with other phytochemicals . Moreover, the anti‐inflammatory activity of extracts from Crataegus azarolus L. seems to be regulated by their remarkable antioxidant activities, through preventing pro‐inflammatory cytokines production, as well as by increasing the secretion of anti‐inflammatory cytokines . In another study, it was also demonstrated that the microcapsules containing procyanidins from hawthorn bark, as also the extract of procyanidins exerted valuable antioxidant and anti‐inflammatory activities, suggesting their future application in dietary and pharmaceutical products, and even as ingredients for functional foods formulation .…”
Section: Major Medicinal Plants Used In Medication System As Anti‐agementioning
confidence: 98%